ASSESSMENT OF QUALITY OF LIFE IN PATIENTS WITH DIABETES MELLITUS TYPE I (Fiep Bulletin - online, 2014)
Objective: Evaluate the quality of life in patients with diabetes mellitus type I using the Brazilian version of the diabetes quality of life questionnaire (DQOL). Methodology: Descriptive study, with a quantitative approach, carried out in March and April 2013, in the 9th Regional Health Care Management Office. The sample consisted of 53 patients with diabetes mellitus type I, who answered to a questionnaire validated for the Brazilian context. Data collection took place after approval by the Research Ethics Committee of Faculdade Santa Maria, under the Protocol 208,689. Results and discussion: According to Cronbach's ? scores, it was found out that the satisfaction of patients with diabetes mellitus type I with regard to the disease is 0.80, the impact that the disease causes is 075, social and vocational concerns correspond to 0.79, the concerns related to diabetes correspond to 0.72, and the total score of the 44 questions is 0.89. Conclusion: This study addresses the positive and negative aspects related to the quality of life of patients with diabetes mellitus type I and it may be applied to action programs of the Brazilian health care system aimed at the care and well-being of users and their caregivers and relatives, who live with a chronic condition.
Keywords: Quality of life; Diabetes mellitus; Diabetes quality of life questionnaire.